Investigation of transvaginal and transabdominal ultrasound and bladder fullness in the evaluation of cervical length in low-risk pregnant women - Feyza Nur İncesu Çintesun (Perinatal Medicine Foundation, 2021)
Objective Cervical length is an important ultrasonographic marker used to predict cervical insufficiency and preterm labor. Our aim in this study was to compare TA and TV cervical lengths in three trimesters and to investigate the effect of bladder fullness on TA measurements. Methods This study was planned as a prospective cross-sectional study and low-risk pregnant women between 11-37 weeks who presented to the hospital were included in the study. The patients were divided into three groups according to their trimesters, and the cervical lengths of the patients were assessed first with TA and then TV ultrasound with a full bladder and then an empty bladder. Results The mean cervical length was 45.6±7.0 cm in first-trimester patients, 42.8±7.0 cm in second-trimester patients, and 41.0±8.5 cm in third-trimester patients. Although TV cervical length was longer in all three trimesters, no statistically significant difference was found between TV and TA ultrasound with a full bladder (p>0.05). When TA ultrasound with empty bladder and TV ultrasound were compared, the TV measurements were found to be statistically significantly longer in each trimester (p<0.05). It was shown that parity number, fetal presentation, and obesity did not affect TV or TA assessment with a full bladder (p>0.05). Conclusion TV and TA assessment with a full bladder were found similar in all three trimesters. TA ultrasound with a full bladder can be safely used for cervical length measurement in low-risk patients in every trimester.